2017
DOI: 10.1111/imr.12540
|View full text |Cite
|
Sign up to set email alerts
|

Allergic airway inflammation: key players beyond the Th2 cell pathway

Abstract: Allergic asthma is characterized by eosinophilic airway inflammation, mucus hyperproduction, and airway hyperreactivity, causing reversible airway obstruction. Accumulating evidence indicates that antigen-specific Th2 cells and their cytokines such as IL-4, IL-5, and IL-13 orchestrate these pathognomonic features of asthma. However, over the past decade, the understanding of asthma pathogenesis has made a significant shift from a Th2 cell-dependent, IgE-mediated disease to a more complicated heterogeneous dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 232 publications
(494 reference statements)
1
65
0
5
Order By: Relevance
“…Their discovery led to the change in nomenclature from Th2-high asthma, which implied that these cytokines are exclusive products of Th2 cells, to type 2. Recent evidence also supports a role of ILC2s in the remodeling and repair of damaged tissue of asthma, disclosing new potential therapeutic target acting on the remodeling process [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Their discovery led to the change in nomenclature from Th2-high asthma, which implied that these cytokines are exclusive products of Th2 cells, to type 2. Recent evidence also supports a role of ILC2s in the remodeling and repair of damaged tissue of asthma, disclosing new potential therapeutic target acting on the remodeling process [16]. …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Although a range of preventive and therapeutic strategies have been applied in the treatment of asthma, its prevalence has rapidly increased across the world, especially in children and young adults. 7,8 Gene expression studies of brushed bronchial epithelial cells in the lower airway have identified different asthmatic phenotypes based on observed expression profiles. 7,8 Gene expression studies of brushed bronchial epithelial cells in the lower airway have identified different asthmatic phenotypes based on observed expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Christianson et al demonstrated elevated IL‐33 and ILC2 levels in BAL of patients with asthma and IL‐33 correlated with disease severity. ILC2s from patients with severe asthma produce more IL‐5 and IL‐13 upon in vitro exposure to IL‐25, IL‐33, and TSLP than those from healthy controls, indicating their pre‐activated state in disease . The disease severity correlates with the level of ILC2 enrichment, as demonstrated by Bartemes et al .…”
Section: Ilc2s In Diseasementioning
confidence: 75%